Tobacco control by public pharmaceutical assistance policies - Gomes, João Carlos de Souza; Souza, Beatriz de Barros (Seven Editora, 2023)
Smoking is responsible for several diseases and millions of deaths every year, being one of the major causes of preventable death in the world. Defined as the chemical dependence on nicotine in cigarettes, its main associated diseases are lung cancer (about 90%), cardiovascular diseases (about 25%), chronic respiratory diseases such as bronchitis and emphysema, and a higher risk of stroke and respiratory infections. The most effective policies to combat this addiction include increasing taxes on tobacco products, banning tobacco advertising, creating smoke-free environments, clearly labeling tobacco products, and offering smoking cessation services. In Brazil, the National Tobacco Control Program (PNCT), created in 1986, and the Anti-Smoking Law (Federal Law No. 9,294/1996), are milestones for pharmaceutical assistance, which assists policies in the treatment of smoking. In the pandemic, this dependence was one of the main comorbidities associated with severe cases of COVID-19, which were better controlled by updated health professionals and acting together to guarantee access to essential treatments and support therapies for smokers. Currently, public policies are needed to raise awareness among the population about the risks of smoking and e-cigarettes, avoiding their indiscriminate and uncontrolled trade, among other measures. In this sense, the 2030 Sustainable Development Goals (SDGs) impose coordinated efforts on countries to implement effective tobacco control policies in an integrated, sustainable and democratic manner, with the participation of civil society and health professionals. DOI:https://doi.org/10.56238/globalhealthprespesc-047